Cyprus Circular Economy Network - (:unkn) unknown (My University, 2026)
ollowing the challenges of recent years, the growing demands from the European Union (EU) for the transition of the economy to a green and circular growth model, as well as the recognition of the significant benefits that circular economy offers to businesses, industry, consumers, environment and the economy, the Cyprus Federation of Employers & Industrialists (OEB) took the initiative to establish the Cyprus Circular Economy Network (CCEN), the first pioneering Circular Economy Network in Cyprus. The Cyprus Circular Economy Network consists of the following parties: The Cyprus Federation of Employers & Industrialists (OEB) – Leading Founding Member The Cyprus International Institute of Management (CIIM) – Founding Member The Cyprus Institute (CyI) – Founding Member The Cyprus University of Technology (CUT) – Founding Member The Cyprus Organisation for Standardisation (CYS) – Founding Member. The ultimate goal of the CCEN is to enable and accelerate the transition of Cyprus economy to a circular and green economy, especially after the COVID-19 pandemic, offering its services in a multilevel stakeholder approach; businesses, academia and public sector, contributing to the achievement of the economic and social resilience of Cyprus, for a sustainable future.